Low-Cost and Portable Sound Reduction Box: Innovation for Acoustic Material Performance Measurement - Budi Purwanto; Melania Hanny Aryantie; Zulfachmi Zulfachmi; Rina Aprishanty (Journal of Engineering and Technological Sciences, 2020)
A sound reduction index (RIc) is a laboratory measurement of the sound insulating properties of a material or building element, commonly conducted using a reverberation chamber and an anechoic chamber (SIC), which requires high expenses. This study aimed to perform RIc analysis using a sound reduction box (SRB) to assess the accuracy and precision of the associated result compared to an SIC. The SRB is a miniature reverberation chamber innovation that is owned by the Center for Research and Development of Quality and Environmental Laboratory (P3KLL). The anechoic chamber is substituted by open space as free-field environment. The methods used in this study are based on ISO 15186-1 and ISO 717-1. Measurement was executed using a sound intensity analyzer and data interpretation was done by employing statistical analysis. The types of insulating materials tested were wood boards made of Shorea sp., Swietenia sp. and Dryobalanops sp. with a thickness of 2 cm and 4 cm. Test material measurement was done using the same measuring instruments, sound generators, sound amplifiers, and personnel. The results show that the RIc values were almost the same for both methods (SIC and SRB). When the weighted sound reduction index (Rw) rating calculated from the RIc was compared between the SIC and the SRB, the results were not statistically different. It is interesting that an SRB can be developed in the future as an alternative device for acoustic materials testing.